فعالية استخدام Quizbot في تعليم اللغة العربية بـ MAN 2 Langsa - Aziz, Muhammad; Meutia Rahmah; Rahmatun Nisak; Khuzaimah Alfisyahrina (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2026)
Arabic language learning at MAN 2 Langsa conducted through conventional methods tends to result in low studeny achievement and learning motivation. Therefore, an innovation in interactive digital learning media such as QuizBot is needed. QuizBot is a chatbot-based digital learning medium that provides interactive quizzes as a practice tool for students. This study aimed to determine the effectiveness of using QuizBot media in improving students’ learning outcomes and satisfaction in Arabic language learning. This study employed a quantitative research method with a pre-experimental one-group pretest-posttest design. The population consisted of 152 tenth-grade students of MAN 2 Langsa, while the sample consisted of 21 students from class X-2 selected through purposive sampling technique. The research instruments included test and a student satisfaction questionnaire. The results showed an improvement in students’ average scores, increasing from 60.71 in the pretest to 76.42 in the posttest. The N-Gain score of 0.3882 was categorized as moderate, while the questionnaire results indicated a student satisfaction level of 81.14%, which falls into the satisfied category. These findings indicate that the use of QuizBot media is effective in improving Arabic language learning outcomes and student satisfaction.   Keywords : Arabic Language Learning, ICT-Based Learning Media, Telegram, Quibot